On the design of mobile applications for Geometry - Fabian, Khristin (2010)
The challenge of extending learning beyond the classroom walls and connecting the curriculum with relevant real world experiences has long been a challenge for mathematics but it is the ubiquity of mobile technologies that has re-sparked the interest to this challenge. Mobile learning carries with it number of potential benefits that mathematics can take advantage off. This study developed a design of a mobile application package for geometry by considering how mobile phones lend themselves as tools for teaching and learning mathematics. The design of the application package consisted of four stages: concept development, design phase, production phase and evaluation phase. The concept phase looked at how mobile devices can support various math learning frameworks. The design phase looked at the design of the learning strategies the mobile application would go by and listed interface requirements that would make the application usable. Two applications were developed in the production phase, both grounded on the constructionist learning framework: a geoboard manipulative and a location-aware application inspired by Logo’s Turtle. The applications were then evaluated by mobile learning experts to check for usability issues.